Avidity and subtyping of specific antibodies applied to the indirect assessment of heterologous protection against Foot-and-Mouth Disease Virus in cattle - Lavoria, Maria de Los Angeles (2012)
Serological assessment of the heterologous response among Foot-and-Mouth Disease Virus (FMDV) strains is mainly performed by virus neutralization test (VNT), liquid phase blocking ELISA and complement fixation assay. In this study two high-throughput ELISA techniques, avidity and IgG subtype ELISA, were developed and used to further characterize heterologous antibody responses in cattle during vaccination and challenge. Both assays were applied to a set of previously characterized sera from animals immunized with an inactivated A24 Cruzeiro/Brazil/55 (A24 Cruzeiro) strain monovalent FMDV vaccine and challenged with the heterologous A/Argentina/2001 (A/Arg/01) strain. Single dilution avidity ELISA assessment showed that animals that were protected against A/Arg/01 challenge had higher avidity antibodies to this heterologous strain than non-protected cattle. Animals with low or even undetectable anti-A/Arg/01 serum-neutralizing titers that passed the heterologous challenge presented higher IgG1/IgG2 ratio than non-protected animals. In this study, the three assessments (VNT and both ELISAs) discriminated between protected and not protected animals against a heterologous challenge. The combination of these techniques may be applied to complement current indirect serological vaccine-matching assessments. The measurement of these qualitative parameters may provide additional information to understand the mechanisms underlying FMD heterologous responses and the induction of cross-protection in cattle.